2019
DOI: 10.1177/2399808319857726
|View full text |Cite
|
Sign up to set email alerts
|

The morphology and circuity of walkable, bikeable, and drivable street networks in Phnom Penh, Cambodia

Abstract: Street network analysis is a growing area in sustainable transportation research. Most academic papers on the topic have, so far, been concentrated in Europe and America, with less attention paid to rapidly growing cities in low income nations. This is problematic because transportation networks are rapidly evolving in developing countries and the impacts of misguided transportation policies (including air pollution and road traffic casualties) are particularly acute. Metrics on the performance of street netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Information and communication technologies (ICTs) have helped transform human societies and contributed to the progress of health, education, and various other sectors ( Yen et al, 2019 ; Sohail et al, 2021c ; Usman et al, 2021a , b ). In recent times, it has become a pertinent question whether ICTs have any impact on the individual personality or not.…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technologies (ICTs) have helped transform human societies and contributed to the progress of health, education, and various other sectors ( Yen et al, 2019 ; Sohail et al, 2021c ; Usman et al, 2021a , b ). In recent times, it has become a pertinent question whether ICTs have any impact on the individual personality or not.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies on urban street networks have been conducted by using OSMnx. Yen et al used circuity as one of the metrics to analyze three street network patterns, namely, walkable, bikeable, and drivable, in Phnom Penh, Cambodia [28]. Their results suggested that urban central areas are more favorable for walking and biking than peripheral districts.…”
Section: Introductionmentioning
confidence: 99%
“…Chetley et al, 2006 study denoted that the internet is capable of improving healthcare and health outcomes in developing economies. Additionally, it can ease communication between healthcare experts and patients ( Bankole et al, 2013 ; Yen et al, 2019 ; Sohail et al, 2021a ). ICT helps in improving public utilities, efficiency, and management of governments.…”
Section: Introductionmentioning
confidence: 99%